Dietary intake of energy and selected nutrients and plasma lipid profile in young women and men with different levels of physical activity - Malara Marzena; Hübner-Woźniak Elżbieta (Sciendo, 2013)
Study aim: The purpose was to assess dietary intake of energy and selected nutrients and plasma lipid profile in young women and men with different levels of physical activity.